عمارة القُرى المبكرة في وادي سُوف - حسونة, عبد العزيز (University of Eloued جامعة الوادي, 2021)
تعتبر وادي سوف من الأقاليم الصحراوية الواقعة على الحواف الجنوبية للكتلة الأوراسية ، تتميز بمناخها الصعب وطبيعتها القاسية يغلب على سطحها ظاهرة الكثبان الرملية التي تزداد ارتفاعا في كلما توغلنا جنوبا . عرفت وادي سوف التعمير البشري منذ عهود قديمة بحكم موقعها الوسط بين عدة أقاليم متقاربة إجتماعيا و ومتنافرة سياسيا ،فكانت بمثابة المعبر والملجأ لفئات دينية أو عرقية هروبا من الإضطهاد الديني أو التسلط السياسي وساعد ذلك على ظهور تجمعات سكانية تحولت بمرور الوقت إلى قرى وبلدات متباينة في الأهمية . تواترت الروايات الشفهية والكتابية أسماء لكثير من هذه التجمعات السكنية التي أختفت التي نحاول في هذه الدراسة الموجزة إستظهار البعض منها وكشف اللثام عنها . Ouadi souf is one of the desert regions located on the southern edges of the Eurasian mass, characterized by its difficult climate and its harsh nature dominated by the phenomenon of sand dunes that increase in height as we move south. Ouadi souf has known human reconstruction since ancient times because of its location between several socially close and politically dissonant territories, it served as a crossing point and refuge for religious or ethnic groups fleeing religious persecution or political domination and helped the emergence of populations that over time turned into villages and towns of varying importance. Frequent oral and written accounts names for many of these communities that have disappeared, which in this brief study we try to conjure some of them and reveal them
مقال